2x-36=5(x+3)

Simple and best practice solution for 2x-36=5(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-36=5(x+3) equation:


Simplifying
2x + -36 = 5(x + 3)

Reorder the terms:
-36 + 2x = 5(x + 3)

Reorder the terms:
-36 + 2x = 5(3 + x)
-36 + 2x = (3 * 5 + x * 5)
-36 + 2x = (15 + 5x)

Solving
-36 + 2x = 15 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-36 + 2x + -5x = 15 + 5x + -5x

Combine like terms: 2x + -5x = -3x
-36 + -3x = 15 + 5x + -5x

Combine like terms: 5x + -5x = 0
-36 + -3x = 15 + 0
-36 + -3x = 15

Add '36' to each side of the equation.
-36 + 36 + -3x = 15 + 36

Combine like terms: -36 + 36 = 0
0 + -3x = 15 + 36
-3x = 15 + 36

Combine like terms: 15 + 36 = 51
-3x = 51

Divide each side by '-3'.
x = -17

Simplifying
x = -17

See similar equations:

| 100=20t+5t^2 | | 4-5X=59 | | 4x-3x=1x | | 6a^2-5a-4=0 | | 5x=6x+31 | | 25.00x=4.50 | | 3y-2+6x=0 | | 2x-6=3x+1-x-2 | | 4x^2+4x=9 | | 2(x+4)-5=2x+13 | | n+5=9+2n-3-8 | | .5(4x-10)=52+3x | | 69=3v | | 3x-6+x+8=42 | | 5xy^2+3xy^2= | | -5w^2+23w-42=0 | | 11=4x-3y | | 0=-16t^2+50t+6 | | 5x-4=3x+2x+3-2+1 | | 72=5c+7c-2c | | n+5=-1-16 | | 2(-3a+5)=2y+3 | | 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 | | 12x-7=27x+3 | | -1x=13 | | 34a-4(5d+2)=36 | | 235=177-x | | -5n-15n=10 |

Equations solver categories